PENINGKATAN MOTIVASI DAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN PROJECT BASED LEARNING - Sediyati, Sukrismi; Ismanto, Bambang; Kristin, Firosalia (Jurnal Holistika, 2018)
ABSTRACTThis study aims to describe the increase in motivation and learning outcomes of grade IV SD Blotongan 02.Project Based Learning’s Model is a learning model that involves all students to solve problems by making projects. This model will be applied in mathematics learning data presentation material IV. This research was conducted in 2 cycles using data methods in the form of learning motivation and test questionnaires. The analysis technique used is qualitative and quantitative data analysis techniques. Learning outcomes increase if there is an increase in completeness of learning outcomes that reaches .70% while learning motivation says if the score is> 75%. In pre-action, the average mathematics learning motivation of students gets a percentage of 60.30%. After giving the action, it increased to 77.0% at the end of the first cycle, and at the end of the second cycle increased to 82.82%. And for student learning outcomes in the pre-action 35.29% cycle 1 increased by 70.58% and reached the success ratio in cycle 2, which was 85, 29%. Based on all classroom action research activities, it can be concluded that through the implementation of project based learning models can increase motivation and learning outcomes of grade IV students of Blotongan 02.  Keywords: motivation to learn, learning outcomes, project based learning ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan peningkatan motivasi dan hasil belajar siswa kelas IV SD Blotongan 02. Model Pembelajaran Project Based Learning adalah model pembelajaran yang melibatkan semua siswa untuk menyelesaikan masalah dengan membuat proyek.. Model ini akan diterapkan dalam pembelajaran matematika materi penyajian data IV. Penelitian ini dilaksanakan dalam 2 siklus dengan menggunakan metode pengumpulan data berupa angket motivasi belajar dan tes. Teknik analisis yang digunakan yaitu teknik analisis data kualitatif dan kuantitatif. Hasil belajar dikatakan meningkat jika terjadi kenaikan ketuntasan hasil belajar yang mencapai .70% sedangkan motibasi belajar dikatakan berhasil jika skor perolehan yang didapat >75%. Pada pratindakan, motivasi belajar  matematika  rata-rata  siswa  memperoleh  persentase  sebesar  60,30%. Setelah diberi tindakan, meningkat menjadi 77,0% pada akhir siklus I, dan pada akhir siklus II meningkat menjadi 82,82%. Dan untuk hasil belajar siswa pada pra tindakan 35,29% siklus 1 meningkat yaitu 70,58% dan mencapai kriteria keberhasilan pada siklus 2 yakni 85, 29 %. Berdasarkan seluruh kegiatan penelitian tindakan kelasdapat disimpulkan bahwa melalui penerapan model project based learning dapat meningkatkan motivasi dan hasil belajar siswa kelas IV SD Blotongan 02. Kata Kunci : Motivasi Belajar, Hasil Belajar, Project Based Learning